Natural History and Consequences of Nonunion in Mandibular and Maxillary Free Flaps. (16th June 2020) - Swendseid, Brian; Kumar, Ayan; Sweeny, Larissa; Zhan, Tingting; Goldman, Richard A.; Krein, Howard; Heffelfinger, Ryan N.; Luginbuhl, Adam J.; Curry, Joseph M.
Abstract : Objective: To describe the natural history of bone segment union in head and neck free flap procedures and detail the association of poor segment union with postoperative complications. Study Design: Case series with chart review. Setting: Single tertiary care referral center. Subjects and Method: Patients with mandibular or maxillary defects reconstructed with osseous or osteocutaneous free flaps were analyzed (n = 104). Postoperative computed tomography or positron emission tomography/computed tomography scans were reviewed for signs of osseointegration and nonunion. Postoperative wound complications were correlated with imaging findings. Result: Thirty‐seven percent of appositions had partial union on nonunion. Appositions between osteotomized free flap segments form complete unions at a higher rate than appositions with native bone (65% vs 53%, P =. 0006). If an apposition shows a gap of ≥1 mm, the chances of failing to form a complete union are greatly increated (79% vs 8%, P =. 0009). Radiographic nonunion was associated with an increased likelihood of postoperative wound complications (40% vs 19%, P =. 025) and in most cases was present before development of complications. Conclusion: Radiographic evidence of partial union or nonunion of free flap osseous segments greatly exceeds reported rates of clinically evident nonunion. Unions likely form between free flap appositions before unions to the native bone. If initial bone segments are >1‐mm apart, the chance of progression to complete union is low. Incomplete osseointegration appears to be a marker for development of wound complications.